Incidence and Patterns of Overuse and Traumatic Injuries among Adolescent Elite Athletes in Canoe Sprint, Handball, and Triathlon - Cassel, Michael; Schomöller, Anne; Risch, Lucie; Engel, Tilman; Joost, Theresa; Stoll, Josefine; Beckendorf, Claudia; Mayer, Frank (Sportverletzung · Sportschaden, 2025)
Adolescent elite athletes in Olympic sports often specialise at an early age, which increases the risk of overuse and traumatic injuries. The knowledge of injury patterns is a key aspect for prevention strategies. However, little is known about adolescent athlete’s injury patterns in most Olympic sports. This study aimed to analyse the incidence and pattern of traumatic and overuse injuries in adolescent elite athletes from three Olympic sports with various physical demands.A retrospective data analysis was performed, including 348 initial orthopaedic consultations of adolescent elite athletes (m/f: 267/81, 15.9±1.7 years, 179±9 cm, 71±11 kg, 648±107 training hours/year). Athletes from handball (n=185), canoe sprint (n=112) and triathlon (n=51) presented at the local sports medicine centre. All consultations included a medical history obtained by a physician, an orthopaedic examination, and a documentation of anthropometric and training-related data. Injury patterns were classified for traumatic and overuse ratio, type, area, structure, and cause of injury. Incidence per 1000 hours (h) of exposure and injury ratio were analysed in the entire cohort and compared between sports.The mean injury incidence was 3.3/1000 h, while overuse injuries occurred approximately twice as often as traumatic injuries (2.0 versus 1.2/1000 h). Sport-specific total injury incidence was lowest in canoe sprint (1.6/1000 h) and highest in handball (4.7/1000 h). The traumatic versus overuse injury ratio was lowest in canoe sprint (0.13) and highest in handball (0.54). Injury incidence increased with age and training hours from 1.0/1000 h in young athletes (12–13 years) to 5.1/1000 h in older athletes (16–17 years). Type, area, structure and cause of injuries differed significantly between athletes of the three sports. Handball players presented with various traumatic and overuse pathologies, mostly located in the lower extremity. Canoeists and triathletes mainly suffered from tendon overload and muscle injuries of the extremities and the lower back.Both the total incidence and the ratio of traumatic versus overuse injuries differ between athletes participating in handball, canoe sprint, and triathlon. Overuse injuries occurred approximately twice as often as traumatic injuries in the present cohort. Further investigation is required to evaluate whether the variety of injuries seen in individual and team sports is to be taken into consideration in the development of prevention strategies.
Keywords: Musculoskeletal; injury profiles; epidemiology; Olympic sports